Terapia według Nietzschego. W stronę wyważonego metafizycznie poradnictwa filozoficznego = Therapy according to Nietzsche. Towards a metaphysically balanced philosophical counseling - Fabjański, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this article, based on the philosophy of Friedrich Nietzsche, I postulate metaphysically balanced philosophical counseling - a practice that, while not neglecting a specific metaphysical vision of the world (which distinguishes philosophical counseling from any other forms of counseling and psychotherapy), does not accept a priori any metaphysical dogmas. The recipient of such counseling, which I call therapeia, is encouraged to inquire into the ontological structure of the world.
Keywords: Nietzsche, Friedrich Wilhelm (filozof niemiecki; 1844-1900); poradnictwo filozoficzne; metafizyka; psychoterapia; dostrojenie od procesu życia; philosophical counseling; metaphysics; psychotherapy; attunement to the life process of life